Locating foreign affiliates in Germany: The case of Swedish MNEs - Henrik Braconier; Karolina Ekholm (Hamburg Institute of International Economics (HWWA), 2001)
This paper uses a dataset on the foreign activities by Swedish manufacturing firms to examine the performance of German affiliates compared with affiliates in other locations. It is found that German affiliates, on average, have higher labour productivity, R&D expenditure per employee and skill-intensity. There is also evidence suggesting that German affiliates are more oriented towards selling in the local market than affiliates in other European countries. We also analyse the effect of labour costs in the Swedish multinational enterprises' (MNEs?) decision to locate in Germany. We find that the location decision is sensitive to the level of wage costs in Germany and in other potential locations in high-income Europe, but not to the level of wage costs in Sweden or low-income countries in Europe. Finally, we find that the cross-wage elasticity showing the effect of increases in labour costs in other high-income locations in Europe on employment in German affiliates of Swedish MNEs is positive, indicating substitutability between the German workers and the workers employed in other high-income countries in Europe. – – Auf der Basis eines Datensatzes über die Auslandsaktivitäten schwedischer Industriefirmen wird die Performance schwedischer Tochtergesellschaften in Deutschland im Vergleich mit denen in anderen Ländern untersucht. Es zeigt sich, dass die deutschen Töchter im Durchschnitt eine höhere Arbeitsproduktivität und höhere FuEAufwendungen pro Beschäftigten aufweisen und mehr qualifizierte Arbeitskräfte beschäftigen. Sie sind stärker auf den lokalen Binnenmarkt orientiert als die Töchter in den anderen europäischen Ländern. Wir untersuchen auch den Effekt der Arbeitskosten auf die Entscheidung schwedischer Multis, in Deutschland zu investieren. Dabei zeigt sich, dass die Standortentscheidung beeinflusst wird vom Niveau der Lohnkosten in Deutschland und an anderen potentiellen Standorten in europäischen Hocheinkommensländern, aber nicht von den Lohnkosten in Schweden oder in europäischen Niedriglohnländern. Schließlich finden wir Evidenz für einen positiven Zusammenhang zwischen den Arbeitskosten in anderen europäischen Hocheinkommensländern und der Beschäftigtenzahl bei den schwedischen Töchtern in Deutschland. Dies deutet auf eine Substitutionsbeziehung zwischen den Arbeitskräften in Deutschland und anderen europäischen Hochlohnländern hin.
Keywords: F23; J23; 330; labor demand; multinational firms; foreign affiliates; Germany; Multinationales Unternehmen; Auslandsniederlassung; Direktinvestition; Schwedisch; Arbeitsnachfrage; Hochqualifizierte Arbeitskräfte; Arbeitskosten; Standortfaktor; Vergleich; Deutschland; Westeuropa; Welt